A randomized lot-to-lot immunogenicity consistency study of the candidate zoster vaccine HZ/su. Issue 48 (4th December 2017) - Strezova, Ana; Godeaux, Olivier; Aggarwal, Naresh; Leroux-Roels, Geert; Lopez-Fauqued, Marta; Van Damme, Pierre; Vanden Abeele, Carline; Vastiau, Ilse; Heineman, Thomas C.; Lal, Himal
Abstract: Background: The risk of developing herpes zoster (HZ) increases with age and is thought to be associated with a decrease in cell-mediated immunity in older adults. The adjuvanted varicella-zoster virus (VZV) glycoprotein E (gE) recombinant subunit vaccine (HZ/su) showed >90% efficacy in the prevention of HZ when administered in adults ≥50 years of age. Here we aim to evaluate immunogenicity consistency of 3 different HZ/su vaccine lots and to assess safety of these lots. Methods: This multicenter, phase III, double-blind, randomized study (NCT02075515), assessed lot-to-lot consistency in terms of immunogenicity of HZ/su and also assessed safety of these lots. Participants aged 50 years or older were randomized (1:1:1) to receive 2 doses of HZ/su, 2 months apart, from 1 out of 3 randomized HZ/su lots (Lots A, B and C). Humoral immunogenicity was assessed pre-vaccination and 1 month post-second vaccination by anti-gE antibody enzyme-linked immunosorbent assay. Lot-to-lot consistency was demonstrated if the 2-sided 95% confidence intervals of the anti-gE geometric mean concentration ratio between all lot pairs were within 0.67 and 1.5. Solicited symptoms were recorded within 7 days and unsolicited adverse events (AEs) within 30 days after each vaccination. Serious AEs (SAEs) and potential immune-mediated diseases (pIMDs) were reported until study end (12 months post-second vaccination). Results: Of 651 participants enrolled in the study, 638 received both doses of the HZ/su vaccine and 634 completed the study. Humoral immune responses were robust and consistency between 3 manufacturing lots was demonstrated. The incidence of solicited symptoms, unsolicited AEs and SAEs was comparable between all lots. Three fatal SAEs, 1 in each lot, were reported, none of which were considered vaccine-related by investigator assessment. Two out of the 8 reported pIMDs were considered vaccine-related by the investigator. Conclusion: The three HZ/su manufacturing lots demonstrated consistent immunogenicity. No safety concerns were identified. Clinical trial registry number : NCT02075515 (ClinicalTrials.gov ).